2021
DOI: 10.1097/bot.0000000000001962
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Safety of Direct Oral Anticoagulants Following Lower Limb Fracture Surgery: A Systematic Review and Meta-analysis

Abstract: Objectives: Venous thromboembolism (VTE) is a well-established complication after many orthopaedic injuries, such as hip and lower limb fractures. The use of direct oral anticoagulants (DOACs, previously termed novel oral anticoagulants) is well-established as thromboprophylaxis after major elective orthopaedic surgery, but not in the nonelective setting. The aim of this study was to investigate the effectiveness and safety of DOACs after nonelective lower limb fracture surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Up to now, several systematic reviews and meta-analyses have been conducted to assess the effectiveness and safety risk of NOACs. Compared with conventional VTE prophylaxis, NOACs was also strongly supported to use in nonelective lower limb fracture surgery, such as after hip fracture ( Waever et al, 2021 ). Similar to our study, Rezapour et al confirmed that rivaroxaban was also shown to be more cost-effective than apixaban and dabigatran in the prevention of VTE after total knee and total hip replacement surgery ( Rezapour et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, several systematic reviews and meta-analyses have been conducted to assess the effectiveness and safety risk of NOACs. Compared with conventional VTE prophylaxis, NOACs was also strongly supported to use in nonelective lower limb fracture surgery, such as after hip fracture ( Waever et al, 2021 ). Similar to our study, Rezapour et al confirmed that rivaroxaban was also shown to be more cost-effective than apixaban and dabigatran in the prevention of VTE after total knee and total hip replacement surgery ( Rezapour et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…ASA and DOAC use have come under investigation of late. Two heterogenous meta-analyses, recently published, suggest favorable findings with regards to VTE reduction, however level one evidence is yet to emerge 268,269 . Both agents are convenient given their more simplistic oral regimens and encouragingly low rates of VTE, but reservations persist concerning hemorrhagic events, particularly in the immediate postoperative period 263,270 .…”
Section: - What Is the Most Optimal Vte Prophylaxis For Patients Unde...mentioning
confidence: 99%
“…Rationale: Venous thromboembolism (VTE) is a significant source of morbidity and mortality following orthopedic surgery 153,154 . The risk of VTE following orthopaedic surgery varies significantly based on many patient and surgical factors 155-159 . It is important to stratify this risk in order to develop an appropriate anticoagulation plan post-operatively 160-162 .…”
Section: - Concerning Vte Risk Which Surgeries Can Be Considered Majo...mentioning
confidence: 99%
“…12 Studies from the last decade have consistently demonstrated the benefits of DOACs over LMWH for VTEp in orthopaedic trauma surgery. 13,14 A recent systematic review and meta-analysis reported significantly reduced deep venous thrombosis rates when Factor Xa inhibiting DOACs were compared to LMWH for VTEp after lower limb fracture surgery. 14 DOACs were also not inferior to LMWH for prevention of mortality, pulmonary embolism and bleeding, both major and minor.…”
mentioning
confidence: 99%
“…13,14 A recent systematic review and meta-analysis reported significantly reduced deep venous thrombosis rates when Factor Xa inhibiting DOACs were compared to LMWH for VTEp after lower limb fracture surgery. 14 DOACs were also not inferior to LMWH for prevention of mortality, pulmonary embolism and bleeding, both major and minor. A RCT not included in the aforementioned study demonstrated reduced VTE risk with no increase bleeding risk, including minor bleeding, when rivaroxaban was compared to LMWH.…”
mentioning
confidence: 99%